The utility of routine laboratory testing in hypoglycaemic emergency department patients. Issue 1 (22nd December 2008) - Sinert, R; Su, M; Secko, M; Zehtabchi, S
Abstract : Background: After treating a hypoglycaemic patient, how in-depth a work-up is required to prevent their next hypoglycaemic episode? Objective: To determine the utility of routine laboratory testing in the management of hypoglycaemia. Methods: A cross-sectional study at two urban teaching hospitals from July 2006 to July 2007. The study included adult patients (⩾18 years) with hypoglycaemia (fingerstick glucose ⩽60 mg/dl (3.33 mmol/l) in the emergency department or altered mental status resolved by glucose or glucagon). Predictor variables were age, gender, medical history, physical examination, hypoglycaemic agent (insulin vs oral hypoglycaemic). Outcome variables were electrolyte abnormality (serum sodium outside the range of 135–145 mmol/l; serum potassium outside the range of 3.5–5.0 mEq/dl), leucocytosis (white blood cell count >15 000/high power field) or urinary tract infection. Continuous data are presented as mean (SD). Categorical data are presented as percentages with 95% confidence intervals. Student's t and Fisher's exact tests were used to compare data when appropriate (α  =  0.05, two-tailed). Results: 291 patients were studied with a mean age of 64 years (SD 16) (range 22–95) 54 women. 200 patients (69%, 95% CI 63% to 74%) had at least one laboratory abnormality. These included newly diagnosed renal failure (23%), pre-existing renal failure (32%), hypokalaemia (8%), hyperkalaemia (11%), leucocytosis (4.2%) and pyuria (19%). No significant difference was found between the rates of abnormal laboratory results in patients on insulin versus those on oral hypoglycaemics. Higher admission rates (p = 0.001) were also observed in patients with abnormal (70%) compared with normal (53%) laboratory results. Conclusion: The high rate of laboratory abnormalities in hypoglycaemic patients justifies routine testing.